2012
DOI: 10.1111/j.1476-4431.2012.00745.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, hematologic, and electrolyte changes with 0.9% sodium chloride or acetated fluids in endurance horses

Abstract: These findings should aid in the design a larger clinical trial to provide further clarification on the effects of type of fluid therapy on clinical and biochemical parameters in endurance horses. The use of 0.9% sodium chloride may not be ideal for the emergency management of endurance horses as it was associated with an increase in plasma chloride concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
4
0
2
Order By: Relevance
“…Historically, saline has been the mainstay fluid of choice in human medicine due to the perception that it is the most physiologically appropriate choice. However, this has been questioned due to concerns regarding the effects of increased chloride load from its administration (58)(59)(60).…”
Section: Balanced Polyionic Vs Salinementioning
confidence: 99%
“…Historically, saline has been the mainstay fluid of choice in human medicine due to the perception that it is the most physiologically appropriate choice. However, this has been questioned due to concerns regarding the effects of increased chloride load from its administration (58)(59)(60).…”
Section: Balanced Polyionic Vs Salinementioning
confidence: 99%
“…Die Elektrolyt-, Laktat-sowie Säure-Base- Bei gesunden anästhesierten Pferden mit alleiniger Verabreichung von 10 ml/kg/h RL konnten keine signifikanten Naund Cl-Veränderungen über eine 150-Minuten-Allgemeinanästhesie festgestellt werden (Boscan et al 2007), ebenso nicht, wenn 5 -10 ml/kg/h RL für 150 Minuten mit 2,5 ml/kg/h 6 % HAES für 60 Minuten kombiniert wurden (Wendt-Hornickle et al 2011). Bei Distanzpferden konnte nach 20 L einer intravenös verabreichten ausgewogenen kristalloiden Flüssigkeit mit Acetat als Buffer eine Erhöhung des Na um 0,68 % und des Cl um 2,94 % beobachtet werden (Fielding et al 2012). In unserer Studie konnten wir die bisherigen Ergebnisse bestätigen.…”
Section: Ergebnisseunclassified
“…Bisherige Studien haben die Anwendung von RL mit und ohne HAES verglichen (WendtHornickle et al 2011), 0.9 % NaCl versus einer ausgewogenen kristalloiden Acetat-Lösung-Infusion untersucht (Fielding et al 2012) und Veränderungen nach HAES-Boli (Ohta et al 2013) …”
Section: Introductionunclassified
“…When given intravenously, isotonic crystalloid administration has predominantly demonstrated effective volume expansive effects in veterinary studies. The described biochemical changes include reductions in packed cell volume (PCV), total plasma proteins (TP), and haemoglobin content which have been presumed as subsequent to haemodilution (Tollofsrud et al 2001;Fielding et al 2012;Valverde et al 2008;Muir et al 2011;Rose et al 1980). Results of multiple studies involving modest to large infusion volumes have consistently found no changes in serum sodium or calcium.…”
Section: Introductionmentioning
confidence: 99%
“…Results of multiple studies involving modest to large infusion volumes have consistently found no changes in serum sodium or calcium. (Tollofsrud et al 2001;Fielding et al 2012;Valverde et al 2008;Rose et al 1980;Rohrig 2012;Rohrig et al 2014). Changes in potassium have varied between null (Tollofsrud et al 2001;Fielding et al 2012;Rose et al 1980;Rohrig et al 2014) to increased (Valverde et al 2008;Rohrig 2012) with intravenous infusion.…”
Section: Introductionmentioning
confidence: 99%